Identifying a Gap in the Project Management Approach of the Online Program Management and University Partnership Business Model - Ramani, Swati; Bradford, George; Dias, Shamini; Olfman, Lorne (Online Learning, 2022)
As the number of online courses increase in higher education, many higher education institutions outsource online course development to an Online Program Management (OPM) provider because of a lack of budget, staff, and technology. Current research indicates that OPM providers often do not have instructional design (ID) services tailored to a specific university. This research uses a case study to analyze a business partnership between a research university and an OPM provider. The Activity Theory conceptual framework was used to direct inquiry and analysis. Results show a miss of the “Empathize” (first stage of Design Thinking) phase in the project management approach from the OPM provider side, which made the process appear more like a start-up company and caused some faculty to lose motivation about the instructional design process. A complete Design Thinking approach from the OPM provider and the university partner are very important to reap the most benefits from this relationship.